Cardiac glycosides use and the risk and mortality of cancer; systematic review and meta-analysis of observational studies. - Mohamed Hosny Osman; Eman Farrag; Mai Selim; Mohamed Samy Osman; Arwa Hasanine; Azza Selim (PLoS ONE)
Background Cardiac glycosides (CGs) including digitalis, digoxin and digitoxin are used in the treatment of congestive heart failure and atrial fibrillation. Pre-clinical studies have investigated the anti-neoplastic properties of CGs since 1960s. Epidemiological studies concerning the association between CGs use and cancer risk yielded inconsistent results. We have performed a systematic review and meta-analysis to summarize the effects of CGs on cancer risk and mortality. Methods PubMed, Scopus, Cochrane library, Medline and Web of Knowledge were searched for identifying relevant studies. Summary relative risks (RR) and 95% confidence intervals (CI) were calculated using random-effects model. Results We included 14 case-control studies and 15 cohort studies published between 1976 and 2016 including 13 cancer types. Twenty-four studies reported the association between CGs and cancer risk and six reported the association between CGs and mortality of cancer patients. Using CGs was associated with a higher risk of breast cancer (RR = 1.330, 95% CI: 1.247-1.419). Subgroup analysis showed that using CGs increased the risk of ER+ve breast cancer but not ER-ve. Using CGs wasn't associated with prostate cancer risk (RR = 1.015, 95% CI: 0.868-1.87). However, CGs decreased the risk in long term users and showed a protective role in decreasing the risk of advanced stages. CGs use was associated with increased all-cause mortality (HR = 1.35, 95% CI: 1.248-1.46) but not cancer-specific mortality (HR = 1.075, 95% CI: 0.968-1.194). Conclusion The anti-tumor activity of CGs observed in pre-clinical studies requires high concentrations which can't be normally tolerated in humans. However, the estrogen-like activity of CGs could be responsible for increasing the risk of certain types of tumors.